HUBUNGAN JENIS BREEDING SITES DAN KEPADATAN LARVA DENGAN KASUS MALARIA DI WILAYAH PT. FREEPORT INDONESIA KABUPATEN MIMIKA TAHUN 2013-2017: PENDEKATAN SPASIAL-TEMPORAL - Wafiyyah Rizki Wiariyanti; E. Elsa Herdiana Murhandarwati; Anis Fuad (Berita Kedokteran Masyarakat (BKM), 2019)
Breeding sites and larvae density with malaria cases in PT. Freeport Indonesia, mimika regency in 2013-2017: spatio-temporal approachPurpose: This study aims to determine the relationship between breeding sites and larval density in malaria cases in the Lowland region of PT. Freeport Indonesia Mimika Regency 2013-2017. Method: This study uses secondary data from PT. Freeport Indonesia in 2013 - 2017. The data used in this study included malaria case data, breeding sites and breeding sites and larval density in the lowland PTFI area from 2013-2017. Data analysis included descriptive analysis to see the distribution picture, bivariate analysis to examine the relationship between variables and spatial analysis to find out the distribution of cases and breeding sites.Results: The number of malaria cases from 2013-2017 in the Lowland PTFI region was 267 (37%) from a total population of 713 people. The highest case occurred in 2014 as many as 70 cases. Distribution of cases based on sex occurs mostly in men, in the age group of 46-50 years, based on the relatively equal employment status between employees and non-employees and based on the location, many occur in Kuala Kencana. Types of breeding sites with larvae density have a significant relationship (p <0.0001), larvae density with malaria cases also have a significant relationship (p 0.0013 and r 0.40) especially density in xpool which has a density of 2.01/dip.Conclusion: Distribution of malaria cases focused on locations where employees live and locations with high mobility. The types of breeding sites are related to larval density. The highest density of larvae is found in breeding sites of the xpool type. Larval density and malaria cases have a significant relationship with larvae density in the xpool breeding site.